2005
DOI: 10.1016/j.biomaterials.2004.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic synthesis of highly ordered degradable dextran-based hydrogels

Abstract: We have prepared unique macroporous and ordered dextran-based hydrogels using a single-step biocatalytic transesterification reaction between dextran and divinyladipate in neat dimethylsulfoxide. These hydrogels show a unimodal distribution of interconnected pores with average diameters from 0.4 to 2.0 mm depending on the degree of substitution. In addition, the hydrogels show a higher elastic modulus for a given swelling ratio than chemically synthesized dextran-based hydrogels. In vivo studies in rats show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Dextran hydrogels can be obtained in various ways, based on either chemical or physical crosslinking. Dextran crosslinked with methacrylate (MA), hydroxyethylmethacrylate (HEMA) have been used as hydrogel implants, microspheres for scaffolds [139][140][141][142][143][144].…”
Section: Dextranmentioning
confidence: 99%
“…Dextran hydrogels can be obtained in various ways, based on either chemical or physical crosslinking. Dextran crosslinked with methacrylate (MA), hydroxyethylmethacrylate (HEMA) have been used as hydrogel implants, microspheres for scaffolds [139][140][141][142][143][144].…”
Section: Dextranmentioning
confidence: 99%
“…For that purpose we developed a photopolymerizable dextranbased hydrogels comprising either insoluble (RGD sequences) or soluble [vascular endothelial growth factor (VEGF 165 )] factors for the preferential differentiation of hESCs into the vascular lineage. Dextran-based hydrogels are biocompatible [7,8], biodegradable [9] and cellnonadhesive [7] which allows one to tailor its cell adhesiveness. The RGD peptide is the adhesive motif found in fibronectin, the earliest and most abundantly expressed extracellular matrix molecule during embryonic vascular development [10].…”
mentioning
confidence: 99%
“…Furthermore, the graft copolymers of acrylamide on different types of cellulose [8] revealed that various properties viz flocculation, solubility, thermal stability, binding strength, water retention and drag reduction effectiveness of the substrate increases. Besides these applications poly(acrylamide) has other multiple applications viz as polymer gel dosimeter [9], for water retention: owing to its high swelling capacity [10], in electrophoresis for separation of protein and DNA samples, as a model for drug delivery systems: for studying controlled drug release profiles [11][12][13].…”
Section: Introductionmentioning
confidence: 99%